Vascular entrapment of the sciatic plexus causing catamenial sciatica and urinary symptoms. Issue 2 (February 2016) - Lemos, Nucelio; Marques, Renato; Kamergorodsky, Gil; Ploger, Christine; Schor, Eduardo; Girão, Manoel
Abstract Aim of the video / Introduction Pelvic congestion syndrome is a well-known cause of cyclic pelvic pain (Ganeshan et al., Cardiovasc Intervent Radiol 30(6):1105–11, 2007). What is much less well known is that dilated or malformed branches of the internal or external iliac vessels can entrap the nerves of the sacral plexus against the pelvic sidewalls, producing symptoms that are not commonly seen in gynecological practice, such as sciatica, or refractory urinary and anorectal dysfunction (Possover et al., Fertil Steril 95(2):756–8. 2011). The objective of this video is to explain and describe the symptoms suggestive of vascular entrapment of the sacral plexus, as well as the technique for the laparoscopic decompression of these nerves. Method Two anecdotal cases of intrapelvic vascular entrapment are used to review the anatomy of the lumbosacral plexus and demonstrate the laparoscopic surgical technique for decompression at two different sites, one on the sciatic nerve and one on the sacral nerve roots. Result After surgery, the patient with the sciatic entrapment showed full recovery of the sciatica and partial recovery of the myofascial pain. The patient with sacral nerve root entrapment showed full recovery with resolution of symptoms. Conclusion The symptoms suggestive of intrapelvic nerve entrapment are: perineal pain or pain irradiating to the lower limbs in the absence of a spinal disorder, and lower urinary tract symptoms in the absence of prolapse of a bladder lesion. In the presence of such symptoms, the radiologist should provide specific MRI sequences of the intrapelvic portion of the sacral plexus and a team and equipment to expose and decompress the sacral nerves should be prepared.